Tailoring Self‐Polarization of BaTiO3 Thin Films by Interface Engineering and Flexoelectric Effect. Issue 23 (2nd November 2016) - Guo, Rui; Shen, Lei; Wang, Han; Lim, Zhishiuh; Lu, Wenlai; Yang, Ping; Ariando,; Gruverman, Alexei; Venkatesan, Thirumalai; Feng, Yuan Ping; Chen, Jingsheng
Abstract : BaTiO3 thin films' self‐polarization can be tuned upward or downward, depending on both the substrate termination and the flexoelectric effect upon varying its thickness. Different atomic stacking sequence leads to different self‐polarization direction of fully strained BaTiO3 films, whereas the internal electric field produced by flexoelectric effect becomes the dominating factor in determining the self‐polarization direction of relaxed BaTiO3 films.